1990
DOI: 10.1021/jf00094a024
|View full text |Cite
|
Sign up to set email alerts
|

Salinomycin residues and their ionophoricity in pig tissues

Abstract: The effect of pretreatment with medicated feed on [14C] salinomycin residue levels in pig tissues was studied. Pigs were fed unmedicated feed or feed medicated with salinomycin at 41 ppm in the diet for 29 days and then dosed with [14C]salinomycin for 8 days. Total drug residue levels were below quantifiable limits of detection of kidney, fat, and muscle but at the tolerance limit of 1800 ppb for liver. In liver, pretreatment tended to lower total residue levels, and unchanged [14C] salinomycin accounted for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…Using a microbiological assay, they were able to detect salinomycin, only occasionally, at concentrations of less than 10 ng/g in muscle and kidney; and to detect it at concentrations of around 10 ng/g in liver of chickens following in-feed administration of 60mg/kg salinomycin, without withdrawal. One other study, by Dimenna et al (1990), reported undetectable levels of [ 14 C]salinomycin in the kidney fat and muscle of pigs treated with 41 mg/kg [ l4 C]salinomycin, without withdrawal. They did, however, detect salinomycin in liver, at a concentration of about l-8ng/g.…”
Section: Discussionmentioning
confidence: 99%
“…Using a microbiological assay, they were able to detect salinomycin, only occasionally, at concentrations of less than 10 ng/g in muscle and kidney; and to detect it at concentrations of around 10 ng/g in liver of chickens following in-feed administration of 60mg/kg salinomycin, without withdrawal. One other study, by Dimenna et al (1990), reported undetectable levels of [ 14 C]salinomycin in the kidney fat and muscle of pigs treated with 41 mg/kg [ l4 C]salinomycin, without withdrawal. They did, however, detect salinomycin in liver, at a concentration of about l-8ng/g.…”
Section: Discussionmentioning
confidence: 99%
“…Salinomycin is able to penetrate blood brain barrier, though the existence of P-glycoprotein could limit its oral availability and brain penetration [54]. Liver is the primary site for metabolizing salinomycin; rapid hepatic biotransformation of salinomycin yields numerous metabolites [55]. The elimination of salinomycin is moderately fast; 24 hours has been suggested as an adequate withdrawal period for salinomycin in chickens [53].…”
Section: Pharmacokinetic Parameters Of Salinomycin As An Anti-coccidimentioning
confidence: 99%
“…Moreover, Atef et al (1993) concluded that the highest concentration of Salinomycin was in liver, kidneys, muscles, fat and heart. They also mentioned that the toxic effect induced by Salinomycin may be due to its action on cellular cations homeostasis (Westley, 1983) or residual effects on tissue cells (Dimenna et al, 1990).…”
Section: Discussionmentioning
confidence: 99%